Efficacy of teacher education institutions and primary schools in teacher preparation in Zimbabwe - Magudu, S.; Gumbo, M.T. (South African Journal of Higher Education, 2019)
The purpose of this generic qualitative study was to examine the efficacy of teacher education institutions (TEIs) and schools in Zimbabwe in regard to partnering for the delivery of teacher education. Data were collected through semi-structured interviews and a focus group discussion (FGD) involving 24 participants and comprising student teachers, college lecturers and mentors. The findings revealed that there was a framework for TEI-schools collaboration in teacher preparation. The efficacy of the partnership was, however, undermined by such factors as inadequate attention being accorded to various aspects that are considered to be central to effective partnerships, i.e. planning, mentoring, TEI visits to schools, communication, and a number of inconsistencies that seemed to characterise the relationship. The findings suggest that the efficacy of the partnership could be enhanced through the recognition of the interdependent nature of the relationship, diversification of areas of TEI-schools joint activity and increased conversations between the partners about issues pertinent to the arrangement. The knowledge derived from the study may provide insights into factors that contribute to undermining the effectiveness of partnerships and the implications of these for the professional development of prospective teachers.